PENINGKATAN KETERAMPILAN DRIBBLING SEPAKBOLA MELALUI MODIFIKASI ALAT RECYCLE - Ferly Sandi Wijaya (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Weight training aplication and exercise tool must be adjusted with athletecharacteristic that want to be trained, for that needed weight training and use exercisetool that tiered by modify recyle tool that being adjusted. The methode that being use isaction research using Kemmis and McTaggart modhel with planning design,observation, action and reflection. The research result showing the increase of footballdribbling skills. It’s proved by the averages on pra siclus which is 51,0 and thepresentage is 20,8%, at first siclus became 63,9 and the presentage is 54,2% and thesecond siclus increasing became 73,3 and the presentage is 87,5%. So it can beconcluded that aplication of modify recycle tool can increasing football dribbling skill.Because of giving weight training that adjusted with athlete characteristic which wantto be trained can make it easier training proces and the athlete.Keyword: Football dribbling, recycle equipment